2022
DOI: 10.1002/joc.7572
|View full text |Cite
|
Sign up to set email alerts
|

Extreme precipitation events in the Austral Chaco region of Argentina

Abstract: This study assesses the intensity, spatial distribution and temporal variability of extreme precipitation events (EPEs) on different time scales relevant to agriculture and water resources during the 1901–2016 period over Argentina's Austral Chaco (ACh). EPEs were identified using a nonparametric approach for the Standardized Precipitation Index (SPI). The leading modes of SPI's variability were detected using the Singular Spectrum Analysis. We also compile and control the quality of precipitation observations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…The 2008/2009 drought in the region was among the most severe in the last 50 years [49,50]. Additionally, several studies have shown an increasing trend of warm days/nights [51][52][53][54] and the occurrence of dry spells [54,55] in the region in the last decades.…”
Section: Introductionmentioning
confidence: 99%
“…The 2008/2009 drought in the region was among the most severe in the last 50 years [49,50]. Additionally, several studies have shown an increasing trend of warm days/nights [51][52][53][54] and the occurrence of dry spells [54,55] in the region in the last decades.…”
Section: Introductionmentioning
confidence: 99%